Economic analysis of the technical characteristics and quality standards of storage and refrigeration units for agricultural products in Lattakia Governorate. - ليلى, جميلة; حيان سليمان ,; وائل حبيب, (Latakia University Journal -Biological Sciences Series, 2023)
The study aimed to identify the technical characteristics of storage and refrigeration units in Lattakia Governorate, and to identify the extent to which these units apply to quality standards for agricultural products. And measures of correlation of various kinds, and multiple regression in order to measure the relationship between the independent dependent variables. The research reached the following results: The factors that significantly affect the quality of storage and refrigeration units within the study sample include the variable of gender, type of cars used in transporting products, characteristics and quality standards of the picking process, type of containers used in picking, distance from the main markets, and the process of cleaning and sterilization, which positively affect the overall quality. . - The total net profit of the coastal unit for storage and refrigeration amounted to about 299.63 million SP, and the production efficiency amounted to 1.39, which is a good indicator for investment. As for the profitability coefficient for the invested capital, it reached 39.4%, which is a good indicator.